Distinct Responses of Modeling‐ and Remodeling‐Based Bone Formation to the Discontinuation of Intermittent Parathyroid Hormone Treatment in Ovariectomized Rats. (30th September 2022) - Wang, Wenzheng; Azar, Tala; Tseng, Wei‐Ju; Pei, Shaopeng; Zhou, Yilu; Jiang, Xi; Dyment, Nathaniel; Liu, X. Sherry
ABSTRACT: Anabolic agents, such as intermittent parathyroid hormone (PTH), exert their treatment efficacy through activation of two distinct bone formation processes, namely, remodeling‐based bone formation (RBF, bone formation coupled with prior bone resorption) and modeling‐based bone formation (MBF, bone formation without prior activation of bone resorption). However, if not followed by an antiresorptive agent, treatment benefit was quickly lost upon withdrawal from anabolic agents. By using in vivo micro–computed tomography imaging and multiplex cryohistology with sequential immunofluorescence staining, we investigated the temporal response of newly formed bone tissue from MBF and RBF and the preexisting bone tissue to withdrawal from PTH treatment and the associated cellular activity in an ovariectomized (OVX) rat model. We first demonstrated continued mineral apposition at both RBF and MBF sites following PTH discontinuation, resulting in an extended anabolic effect after 1‐week withdrawal from PTH. It was further discovered that MBF sites had a greater contribution than RBF sites to the extended anabolic effect upon early withdrawal from PTH, evidenced by a higher percentage of alkaline phosphatase‐positive (ALP+) surfaces and far greater bone formation activity at MBF versus RBF sites. Furthermore, significant bone loss occurred after 3 weeks of discontinuation from PTH, resulting from marked loss of newly formed bone tissue from RBF and preexisting bone tissue prior to treatment. In contrast, MBF surfaces had a delayed increase of tartrate‐resistant acid phosphatase activity following PTH discontinuation. As a result, newly formed bone tissue from MBF had greater resistance to PTH discontinuation–induced bone loss than those from RBF and preexisting bone. Understanding various responses of two distinct bone formation types and preexisting bone to anabolic treatment discontinuation is critical to inform the design of follow‐up treatment or cyclic treatment strategies to maximize treatment benefit of anabolic agents. © 2022 American Society for Bone and Mineral Research (ASBMR).